O problema da fundamentação da universalidade do juizo de gosto na Crítica da faculdade de julgar - Carolina Miranda Sena (2023)
This research aims to investigate the universality and necessary validity of judgments of taste and their a priori principle in the Critique of the power of judgment. We argue that the “Analytic of the beautiful” does not definitively ground the universality and necessary validity of judgments of taste, on the contrary, it deepens the problem. With an “Analytic of the beautiful” still to deduce the a priori principle of the power of judgment and legitimizing the universality and necessary validity of the judgment of taste, Kant arrives at a “Deduction of judgments of taste”. An unsatisfactory deduction, in turn, causes the investigation to fall into an antinomy of taste. It is only in the “Dialectic of the Aesthetic Power of Judgment”, with the solution of the antinomy of taste, that Kant gives a definitive answer to his investigation regarding the universality and necessary validity of the judgment of taste, resorting to the transcendental concept of reason of the supersensible, which has its determining ground in the concept of the supersensible substratum of humanity. We will provide an interpretation of such concepts as a response to the “Dialectic of the Aesthetic Power of Judgment” to then understand whether the universality and necessary validity of judgments of taste are legitimized in the arguments of the Critique of the power of judgment.